Antibiotic Resistance: Investigating the Prevalence of Antibiotic Resistance in E. Coli Infections among Patients Treated with Ciprofloxacin versus Amoxicillin : Antibiotic Resistance in E. Coli Infections among Ciprofloxacin versus Amoxicillin Patients - Marfani, Suhail; Khan, Nadiya; Zubair, Muhammad Ali; Ali, Syed Liaquat; Anwar, Khawar; Islam, Ayesha (Pakistan Journal of Health Sciences, 2025)
Among all gram-negative organisms that cause bacteremia, the most frequent one is Escherichia coli. Objectives: To determine the prevalence of antibiotic resistance towards E. coli infections in patients treated with ciprofloxacin and amoxicillin. Methods: This cross-sectional descriptive study was carried out at the Shahida Islam Medical College and Hospital for six months from July 2024 to December 2024. Isolates of specimens from various samples, such as blood, urine, stool, pus of the ear and skin were included. Isolates positive for Escherichia coli were included, while isolates from other organisms were excluded. Antibiotic sensitivity towards Ciprofloxacin and Amoxicillin was tested. SPSS version 25.0 was used for data analysis. Chi-square test was applied for statistical analysis, keeping p<0.05 as statistically significant. Results: The study analyzed 208 E. coli isolates, mostly from patients over 55 years and presenting with outpatient infections. Antibiotic resistance was significantly higher to amoxicillin (68.75%) compared to ciprofloxacin (41.35%) (p<0.001). Only 9.62% of isolates were sensitive to amoxicillin, while 44.71% were sensitive to ciprofloxacin. These findings highlight a concerning prevalence of resistance, particularly against amoxicillin, among E. coli infections. Conclusions: The results of this study reported a higher prevalence of antibiotic resistance to Amoxicillin when compared with the resistance towards Ciprofloxacin. Further, multicenter studies with a greater sample size would be better able to authenticate the findings observed in this research.